Implications of Preliminary Treatment Using Effective Microorganisms on the Chemical Composition of Daluga Starch Processing Waste (Cyrtosperma merkusii) - Moko, Emma Mauren; Rawung, Livana Dethris; Rahardiyan, Dino; Lihiang, Anatje; Wantania, Johana Zusye; Ngangi, Crescentia Mishi (Jurnal Kimia Fullerene, 2026)
Daluga (Cyrtosperma merkusii) starch processing yields waste with 70% of its total weight consist of organic biomass materials that can be utilized as advanced composite biomass materials, a potential base for reinforcing materials. Processing the Daluga waste (debris) requires stages of pretreatment and activations to eliminate inhibiting agents within the hydrolisis process (fermentation process). The purpose of this research is to understand the effects of biological pretreatments using the Effective Microorganism (EM4) bacterial consortium towards the chemical properties of Daluga debris. The chemical compositions of debris Daluga before and after each treatment were determined by NDF and Van Soest method for observing the cellulose, hemicellulose, lignin, fiber, ash content, crude protein, silicate and crude fat. These parameters were analysed following the methods outlined in the Indonesian National Standard (SNI 01-2891-1992) and while protein and carbohydrate content was measured with the Dumas combustion method. Results indicated that lignin concentration after delignification process decreased considerably to 1.80 ± 0.07% although lignin content of these Daluga debris initially wasn’t so high to begin with 4.11 ± 0.02%. Herewith, hemicellulose also decreased giving an appearance for the increase and exposure of cellulose. Thus, providing a clear path to further processing the cellulose to advance cellulosic materials such as cellulose nano crystals (CNC).